ARTIFICIAL INSEMINATION OF SENDURO GOAT AS GENETIC PRESERVATION AND DISSEMINATION OF VARIAN PROCESSED MILK GOAT PRODUCTS AT LUMAJANG DISTRICT - Pratiwi Trisunuwati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
The objective of this study was to disseminate the technology of Artificial Insemiation (AI) and managenet of Milk Processing. This activity expected to help the Ettawa goat farmer to over coming their problems which sub sequentlyit can be improve their income.The method susedin this study was to give in sight knowledge and simple technology to the selected Ettawa goat partner group.The result of these activities were achieved the result of loco goat artificial insemination about 77% Conception rate, so that farmers will accept this technology. In other ways showed the Ettawa goat farmer as partner group receive the strengthening of their business wether kid product and milk procesing product.Hopefully farmers will adopted the technique of selecting superior sires, livestock management,and milk processing technology production plant.